A preliminary study on methylphenidate-regulated gene expression in lymphoblastoid cells of ADHD patients. (April 2015) - Schwarz, Ricarda; Reif, Andreas; Scholz, Claus-Jürgen; Weissflog, Lena; Schmidt, Brigitte; Lesch, Klaus-Peter; Jacob, Christian; Reichert, Susanne; Heupel, Julia; Volkert, Julia; Kopf, Juliane; Hilscher, Max; et al.
Abstract: Objectives. Methylphenidate (MPH) is a commonly used stimulant medication for treating attention-deficit/hyperactivity disorder (ADHD). Besides inhibiting monoamine reuptake there is evidence that MPH also influences gene expression directly. Methods. We investigated the impact of MPH treatment on gene expression levels of lymphoblastoid cells derived from adult ADHD patients and healthy controls by hypothesis-free, genome-wide microarray analysis. Significant findings were subsequently confirmed by quantitative Real-Time PCR (qRT PCR) analysis. Results. The microarray analysis from pooled samples after correction for multiple testing revealed 138 genes to be marginally significantly regulated due to MPH treatment, and one gene due to diagnosis. By qRT PCR we could confirm that GUCY1B3 expression was differential due to diagnosis. We verified chronic MPH treatment effects on the expression of ATXN1, HEY1, MAP3K8 and GLUT3 in controls as well as acute treatment effects on the expression of NAV2 and ATXN1 specifically in ADHD patients. Conclusions. Our preliminary results demonstrate MPH treatment differences in ADHD patients and healthy controls in a peripheral primary cell model. Our results need to be replicated in larger samples and also using patient-derived neuronal cell models to validate the contribution of those genes to the pathophysiology of ADHD and mode of action of MPH.